The epigenetic regulator Mll1 is required for Wnt-driven intestinal tumorigenesis and cancer stemness - Johanna Grinat; Julian Heuberger; Ramon Oliveira Vidal; Neha Goveas; Frauke Kosel; Antoni Berenguer-Llergo; Andrea Kranz; Annika Wulf-Goldenberg; Diana Behrens; Bálint Melcher; Sascha Sauer; Michael Vieth; et al. (Nature Communications, 2020)
Intestinal cancer stem cells (CSC) are associated with colon cancer. Here, the authors show that Wnt/beta-catenin signalling in CSC requires the epigenetic regulator Mll1 to promote stemness and tumourigenesis in murine and human colon cancer models.